Pervasive game design to evaluate social interaction effects on levels of physical activity among older adults. (June 2019) - Santos, Luciano HO; Okamoto, Kazuya; Hiragi, Shusuke; Yamamoto, Goshiro; Sugiyama, Osamu; Aoyama, Tomoki; Kuroda, Tomohiro
Introduction: Promoting active lifestyles among older adults can bring drastic benefits for their quality of life. The innovative mechanics of pervasive games – that mix real and virtual worlds – can further engage and motivate elderly people into that goal. Using social interaction as a study case, we designed and evaluated the feasibility of a pervasive game to investigate how game design elements can affect the levels of physical activity of older adults. Methods: A mobile, location-based pervasive game was developed, and a study with community dwelling elderly volunteers from Kyoto, Japan was performed to evaluate its feasibility as an experiment system. Results: Participants reported that the theme and visual style of the game was adequate, and that game rules and goals could be easily understood. The game was considered enjoyably challenging and engaging. Further analysis showed that next iterations of the system must pay special attention to the level of complexity of controls, and that new ways to connect players when there are few people playing or when they are too far apart are necessary. Conclusions: The design allowed to test for variations on pervasive mechanics and was effective to engage elderly people, encouraging further investigation.